2016
DOI: 10.1021/acs.est.6b03261
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Reductive Decomposition of Perfluorooctanesulfonate in a High Photon Flux UV/Sulfite System

Abstract: Hydrated electron (e) induced reduction techniques are promising for decomposing recalcitrant organic pollutants. However, its vigorous reactivity with copresent scavenging species and the difficulty in minimizing the competitive reactions make the proportion of e participating in pollutant decomposition low, reflecting by slow decomposition kinetics. In this study, a high photon flux UV/sulfite system was employed to promote e production. Its feasibility in enhancing a notorious recalcitrant pollutant, PFOS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
140
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(150 citation statements)
references
References 47 publications
9
140
0
1
Order By: Relevance
“…Recently, efficient degradation of some halogenated organic compounds (HOCs) and hazardous oxoanions was achieved through UV-activated (bi)sulfite (S(IV)) reduction (abbreviated as UV/S(IV)) [1][2][3], which is classified as a hydrated electron (e − aq )-based advanced reduction process (e − aq -ARP). However, besides the valid concentration of S(IV) (main precursor of e − aq ), UV photon absorbance by S(IV) dominates the production efficiency of e − aq for this reduction process [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, efficient degradation of some halogenated organic compounds (HOCs) and hazardous oxoanions was achieved through UV-activated (bi)sulfite (S(IV)) reduction (abbreviated as UV/S(IV)) [1][2][3], which is classified as a hydrated electron (e − aq )-based advanced reduction process (e − aq -ARP). However, besides the valid concentration of S(IV) (main precursor of e − aq ), UV photon absorbance by S(IV) dominates the production efficiency of e − aq for this reduction process [4].…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that NO 3 − has a negative influence on the degradation of PFOA. Gu et al used a similar system and degraded 98% of PFOS at 25 °C and a pH of 9.2 with a defluorination rate of approximately 50% after 30 min [ 88 ]. Bentel and co-workers operated the UV/sulphite system with a higher pH of 12 [ 75 ].…”
Section: State-of-the-art Liquid Reactionsmentioning
confidence: 99%
“…What's more, a short electron pathway between the GQDs interior and the surface due to the quantum size can enhance the electron transfer as well [39]. GQDs acted as the electron 15 donors in this process, in which electrons can be easily transferred to the surface of SiC nanoparticles. And then PFOS, which accumulated on the surface of SiC due to the surface-active properties, would act as the final electron acceptor for the electron-withdrawing property of sulfonate group.…”
Section: Figure 5 Herementioning
confidence: 99%
“…, the branched PFOS decomposed much faster than the linear isomers [15,22]. It was because that photon and e aq directly reacted with PFOS molecule in solution, and the C-F bond in branched isomers was more vulnerable to reductive decomposition than the linear isomers for the higher electron affinity [41].…”
Section: -mentioning
confidence: 99%
See 1 more Smart Citation